2016
DOI: 10.3904/kjim.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year experience of esophageal endoscopic submucosal dissection of superficial esophageal neoplasms in a single center

Abstract: Background/AimsEndoscopic submucosal dissection (ESD) of a superficial esophageal neoplasm (SEN) is a technically difficult procedure. We investigated the clinical outcomes of ESD to determine its feasibility and effectiveness for the treatment of SEN.MethodsPatients who underwent ESD for SEN between August 2005 and June 2014 were eligible for this study. The clinical features of patients and tumors, histopathologic characteristics, adverse events, results of endoscopic resection, and survival were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 42 publications
1
44
2
Order By: Relevance
“…In particular, stricture is a major concern that is associated with impaired patient's quality of life. The reported incidence rate of post‐endoscopic mucosal resection (EMR) or post‐ESD esophageal strictures is 6.5%‐16.7% . Furthermore, recent studies have reported that resection margins extending into >75% of the entire esophageal circumference, a histological invasion depth of M2, and mucosal defect >30 mm in longitudinal length were independent risk factors for post‐ESD stricture .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, stricture is a major concern that is associated with impaired patient's quality of life. The reported incidence rate of post‐endoscopic mucosal resection (EMR) or post‐ESD esophageal strictures is 6.5%‐16.7% . Furthermore, recent studies have reported that resection margins extending into >75% of the entire esophageal circumference, a histological invasion depth of M2, and mucosal defect >30 mm in longitudinal length were independent risk factors for post‐ESD stricture .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have reported that resection margins extending into >75% of the entire esophageal circumference, a histological invasion depth of M2, and mucosal defect >30 mm in longitudinal length were independent risk factors for post‐ESD stricture . The rate of esophageal stricture has been reported to be as high as 45.5%‐92% in patients with a mucosal defect affecting >75% of the esophageal circumference . Typically, an endoscopic balloon dilatation (EBD) is performed both to treat and prevent esophageal strictures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases showing tumor invasion to the muscularis mucosa (m3) or the submucosa < 200 μm from the muscularis mucosa (sm1), ER should be decided based on the risk of lymph node metastasis because the incidence of lymph node metastasis is known to be associated with the depth of invasion [23,31]. There have been efforts to expand the indications for ESD, based on reported favorable outcomes of ER for m3 or sm1 tumors [11,32,33]. One study recommended ER when the SEN had a size less than 25 mm, a lamina propria invasion width of less than 2,500 μm, and no evidence of lymphatic invasion [33].…”
Section: Discussionmentioning
confidence: 99%